Theology of Prosperity: A New Testament Perspective - Hill, Judith L. (African Journol of Evangelical Theology, 2009)
The article begins with an examination of the first-century understanding of prosperity, first in the Jewish culture and then in the Greco-Roman context. Next, it examines Jesus and Paul with respect to their personal example and their advice to others concerning wealth. Finally, it proposes a few questions to help us determine our perspective today, as evangelicals, with respect to the subject of prosperity. Thus, instead of being a continuous “film” of what the NT says about prosperity, the article presents a few discrete “photos,” snapshots that are somewhat disparate but nevertheless revelatory.
free